Union Busting Dalam Hukum Ketenagakerjaan di Indonesia - Robi'atul Adawiyah; M.Tanzil Multazam; Rifqi Ridlo Phahlevi (Indonesian Journal of Law and Economics Review, 2017)
Labor is a profession that many people have, we often encounter cases in the workspace namely union busting or through dismissal tactics or transfer of workplaces to workers who are active in association, which begins with discrimination. This study aims to explore and analyze the labor law in handling union busting cases, using the normative method namely through the approach of legislation and conduct analysis by looking at ILO conventions. Based on this analysis it can be concluded, that in the labor law there are loopholes that make employers stiil often discriminate, with several real events in Indonesia and other countries.